Intercultural competence development: the perceptions of Chinese visiting scholars sojourning abroad - Zhang, Ling (2016)
Considering the increasing number of Chinese scholars being sent to foreign countries to study as visiting scholars as well as limited research focusing on examining their intercultural competence development while sojourning abroad, it is important to examine their perceptions of the factors affecting their intercultural competence development during their sojourning abroad. A mixed-methods design was employed for this study. Quantitatively, using generalizability theory (Cronbach, Gleser, Nanda, & Rajaratnam, 1972) as a theoretical framework, this study examined differences in 85 Chinese visiting scholars’ ratings of the factors affecting their intercultural competence development during their sojourning abroad across sex (i.e., male and female), age (i.e., younger than 40 years old, 40-50 years old, and older than 50 years old), country of study (i.e., the United States and the United Kingdom), and length of study (i.e., 3-6 months, 7-12 months, and more than 12 months). Qualitatively, this study used ten semi-structured interviews (i.e., 5 interviews with Chinese visiting scholars studying in the United States and 5 interviews with Chinese visiting scholars studying in the United Kingdom) to gain Chinese visiting scholars’ perceptions of the factors affecting their intercultural competence development during their sojourning abroad. Results show that there were significant differences in the ratings of certain factors in terms of their impact on the development of intercultural competence as evaluated by the 85 Chinese visiting scholars across sex, country of study, age, and length of study. Further, the variables sex, country of study, age, and length of study did generate different results in terms of the sources of rating variation of the impact of the factors on Chinese visiting scholars’ intercultural competence development. Furthermore, both Chinese culture and the host country culture affect Chinese visiting scholars’ intercultural competence development while they are studying abroad. Finally, Chinese visiting scholars’ study abroad experience continues to impact their interpersonal communication after they have come back to China. Important educational implications for Chinese visiting scholars as well as American and British professors and administrators are discussed.